PENERAPAN TERAPI KOMPRES AIR HANGAT UNTUK MENGURANGI NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III DI RUMAH SAKIT UMUM ASRI PURWAKARTA - Dina Hartini,; Grace Evelyn, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Back pain in pregnant women is an uncomfortable response that is often felt by pregnant women. Usually back pain will appear when the gestational age enters 7 months. Back pain is a natural thing to happen, but if back pain in pregnant women is allowed t continue it will interfere with daily activities or activities, so that they will experience difficulties in their activities (Mafikasari & Kartikasari, 2015). The results of research on pregnant women in various regions of Indonesiareached 60-80% of people who experienced lower back pain during their pregnancy (Apriliyanti Mafikasari, Ratih Indah Kartikasari, 2015) Based on Data from RSU Asri Purwakarta, 2022 in October reached 355 mothers in November with 99 There are more pregnant women in the third trimester with a spontaneous post partum final diagnosis and experience back pain. Based on this research, it focuses on the application of warm water compress therapy with the aim of reducing low back pain in third trimester pregnant women. After applying warm water compress therapy for 3 consecutive days, the method used in this study is the single subject method, namely descriptive research which is described systematically and factually. The design used in research is campus studies, namely studies to explore problems and applications. Methods of data collection is done by interviews, direct observation and documentation. The client is a third trimester pregnant woman with low back pain who is being treated at RSU Asri Purwakarta. The evaluation method of data analysis was carried out every dayafter the application of the therapy. The results of the study found that the application of warm water compress therapy in third trimester pregnant women to reduce back pain with a pain score of 2